2013
DOI: 10.1089/aid.2012.0266
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Immunological Response in Predicting Virological Failure

Abstract: In HIV-infected individuals on antiretroviral therapy (ART), the decision on when to switch from first-line to second-line therapy is dictated by treatment failure, and this can be measured in three ways: clinically, immunologically, and virologically. While viral load (VL) decreases and CD4 cell increases typically occur together after starting ART, discordant responses may be seen. Hence the current study was designed to determine the immunological and virological response to ART and to evaluate the utility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 15 publications
1
14
1
Order By: Relevance
“…2 Adjusted for age (continuous), ethnicity and gender/likely risk for HIV acquisition, and treatment regimen. 3 To calculate AIC analysis was restricted, separately for analysis of 1 and 3 month measures, to patients who had VL, pre-ART VL and CD4 count recorded.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Adjusted for age (continuous), ethnicity and gender/likely risk for HIV acquisition, and treatment regimen. 3 To calculate AIC analysis was restricted, separately for analysis of 1 and 3 month measures, to patients who had VL, pre-ART VL and CD4 count recorded.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, baseline VL has been shown to be associated with the probability of achieving VL <500 copies/ml [5][6][7][8][9]. Early VL measures have previously been shown to be a good predictor of treatment failure by 6-12 months [3,4]. Furthermore, a handful of studies have looked at relationships between the early viral response to ART and longer-term viral response results after 6-12 months of ART [4,[7][8][9].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As TAHOD participating sites were selected from major HIV referral centres, with some being the only site representing their country, it was expected that there would be variability in treatment protocols and clinical care across these sites. For example, the World Health Organization (WHO) 2013 guidelines recommend VL testing as the preferred method to monitor ART failure due to poor correlation of other monitoring methods with VL failure[4, 11, 12]. However, in resource-limited settings, VL monitoring may not form part of routine clinical care due to its high cost, or lack of resources and infrastructure.…”
Section: Discussionmentioning
confidence: 99%
“…The WHO advise29 that VL levels of >5,000 copies/mL indicate persistent treatment failure, although these levels would not be tolerated in high-income countries where a VL of >200 copies/mL is considered a loss of virological control. In the absence of VL testing availability, immunological monitoring is considered to indicate treatment failure, although falls in CD4 count correlate less well with virological failure 43–45. In the absence of VL and CD4, syndromic management is again used to indicate the need for treatment switching.…”
Section: Tools Used To Monitor Art In High-income Countriesmentioning
confidence: 99%